KEDUDUKAN ARTIFICIAL INTELLIGENCE DALAM SISTEM HUKUM INDONESIA ANALISIS NORMATIF ANTARA SUBJEK HUKUM DAN INSTRUMEN TEKNOLOGI - Rifa Zulkarnain; Rahmayanti Rahmayanti (Penerbit Lafadz Jaya, 2026)
The rapid development of Artificial Intelligence (AI) as an increasingly autonomous technology has raised new legal challenges, particularly concerning its legal status within the legal system. This study aims to analyze the position of Artificial Intelligence in the Indonesian legal system, examine the possibility of AI as a legal subject, and explore the juridical implications of its classification as either a legal subject or a technological instrument. This research employs a normative juridical method with statutory and conceptual approaches. The results indicate that within the Indonesian legal system, Artificial Intelligence is not recognized as a legal subject but is instead positioned as a technological instrument or legal object. AI does not fulfill the essential elements required of a legal subject, such as free will, legal consciousness, and the capacity to bear rights and obligations independently. Consequently, legal liability arising from the use of AI remains attributed to human actors, including developers, users, and corporations. The notion of recognizing AI as a legal subject remains largely theoretical and is not yet applicable within the Indonesian legal context, particularly in criminal law, which requires the element of fault (mens rea). This study recommends the need for legal reform through comprehensive regulations governing the use of AI, as well as the development of adaptive liability models, such as risk-based liability, to ensure legal certainty, justice, and legal utility.